Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja Usahatani Kopi Liberika Pada Era New Normal Covid-19 di Kabupaten Tanjung Jabung Barat - Ningsih, Rozaina; Sativa, Fendria; damayanti, yusma (Universitas Batangahari Jambi, 2024)
Smallholder coffee has a very important role, it can be seen that most (93%) of coffee production comes from smallholderPlantations. However, the condition of farm management in smallholder coffee is on average still less good compared to the condition of Large State Plantations. There are several main problems in smallholder coffee plantations, namely the lack of productivity and the quality of products that still do not meet the requirements for export. West Tanjung Jabung Regency is one of the regencies in Jambi Province whose residents cultivate coffee plantations. Some of the coffee grown in West Tanjung Jabung Regency is the Liberica type, which can grow on peatlands. The area increased from 2016-2018 but was not followed by an increase in production. This study aims to analyze the productivity the factors that influence it during the new normal covid-19 in Tanjung Jabung Barat Regency. The research sampling technique was carried out using the Random Sampling method. The analysis method uses tabulation method data then continued with multiple linear regression. factors that affect labor productivity are proven to be significant Simultaneously, meaning that age, family dependents, farming experience and labor wages together have a significant effect on labor productivity. The partial test concluded that the variables of age and farming experience had no significant effect on labor productivity while the number of dependents and labor wages had a significant effect on labor productivity.